Microbiological Contamination of Retail Meat from Mizoram (India) with Special Reference to Molecular Detection and Multi-Drug Resistance of Escherichia coli - Debbarma, Mujesh; Deka, Devajani; ChaaTolenkhomba, Thingujam; Rajesh, Justus B. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Food articles serve as a common vehicle for transmitting many pathogenic and non-pathogenic microorganisms to humans, and many of these organisms may have developed multidrug resistance. Meat may act as a vehicle for transferring multi-drug-resistant organisms to the consumers. In the present study, a total of 180 (retail beef, N = 90 and chicken meat, N = 90) samples were collected from 3 districts of Mizoram and analyzed for the level of microbial contamination, isolation, and molecular detection of Escherichia coli (E. coli) and its drug resistance pattern. Unacceptable levels of total viable count (TVC) and Escherichia coli count (ECC) were recorded in retail beef and chicken. On PCR assay-based confirmation, E. coli was detected in beef (83.33%) and chicken (80.00%). Significantly (p ≤0.01) lower prevalence of E. coli was recorded in chicken meat from Champhai district (63.33%) than Aizawl (86.67%) and Kolasib (90.00%) districts. Resistance of E. coli strains to amoxicillin was highest with detection of MDR E. coli from beef (42.67%) and chicken (56.94%), indicating public health concerns.